Women’s experiences on the use of Implanon as a contraceptive method in a selected primary healthcare facility in KwaZulu-Natal - Lucky N. Mgobhozi (AOSIS, 2021)
Background: The South African department of health recently introduced subdermal Implanon contraceptive implant with the aim to reduce teenage pregnancy and maternal mortality. First used in all public healthcare facilities across the country since early 2014, this method of contraception has been described as highly effective. However, some women have reported unbearable side effects, forcing them to remove the contraceptive implant early before its expiry date. Negligible emphasis has been placed on staff training and development to equip the nurses with new protocol and policies on Implanon.